Effect of Polymer Network Architecture on Adsorption Kinetics at Liquid–Liquid Interfaces: A Comparison Between Poly(NIPAM-co-AA) Copolymer Microgels and Interpenetrating Network Microgels - Galina A. Komarova; Elena Yu. Kozhunova; Rustam A. Gumerov; Igor I. Potemkin; Irina R. Nasimova (Gels)
Understanding the adsorption features of polymer microgels with different chemical compositions and structures is crucial in studying the mechanisms of respective emulsion stabilization. Specifically, the use of stimuli-responsive particles can introduce new properties and broaden the application range of such complex systems. Recently, we demonstrated that emulsions stabilized by microgels composed of interpenetrating networks (IPNs) of poly-N-isopropylacrylamide (PNIPAM) and polyacrylic acid (PAA) exhibit higher colloidal stability upon heating compared to PNIPAM homopolymer and other relevant PNIPAM-based copolymer counterparts. In the present work, using pendant drop tensiometry, we studied the evolution of water–tetradecane interfacial tension during the adsorption of PNIPAM-PAA IPN particles, comparing them with single-network P-(NIPAM-co-AA) and PNIPAM microgels. The results showed that, despite having the same chemical composition, copolymer particles exhibit completely different adsorption behavior in comparison to other microgel architectures. The observed disparity can be attributed to the nonuniform distribution of charged acrylic acid groups within the P-(NIPAM-co-AA) network obtained through precipitation polymerization. Oppositely, the presence of IPN architecture provides a uniform distribution of different monomers inside respective microgels. Additionally, hydrogen bonding between PNIPAM and PAA subchains appears to reduce the electrostatic energy barrier, enhancing the ability of IPN particles to successfully cover the liquid interface. Overall, our findings confirm the efficiency of using PNIPAM-PAA IPN microgels for the preparation of oil-in-water emulsions and their stability, even when the temperature rises above the lower critical solution temperature of PNIPAM.